Use of the Quizizz Application on Student Learning Interest at MTsN 2 Pelalawan - Iin Nurjannah; Bambang Samsul Arifin; Muhammad Hilmi Maulana Al-Arief; Muhammad Muhammad (Jurnal Smart: Sosial Ekonomi Kerakyatan, 2023)
In the learning process, creating an environment that stimulates active student participation is very important, because students will more easily understand the concepts taught when actively involved. This study aims to determine the extent to which learning media using the Quizizz application affects student interest in learning within the scope of fiqh subjects at MTsN 2 Pelalawan. Qualitative research design using documentation and observation study techniques is used in order to achieve research objectives. The results of the study show that the use of the Quizizz application as a learning model that involves students in answering questions is an effective solution to increase interest in learning and understanding of fiqh subject matter. Quizizz brings a number of benefits because it is game-based, utilizing shared game elements that make the learning process more interesting and interactive. The game features such as avatars, themes and entertainment music provided by Quizizz make it particularly suitable for online learning.